PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA TANGRAM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - ririn prihantini; Azin Taufik; Mohamad Riyadi (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
The aim of this study was determine the differences of the ability of mathematical creative thinking and the differences in the increase between classes using Problem Based Learning (control class) and the class that uses a model of Problem Based Learning with tangram. The research method used is quasi experimental design of non-equivalent pre-test-post-test control group design. The population in this study were all students of class VII junior high school in Kuningan in the even semester of the academic year 2017/2018.  Through purposive sampling technique, 2 classes of 10 classes were selected as samples where the class VIIA as the control class and VIIB as experimental class with a total sample of 70 students. Data collection techniques were obtained through mathematical creative thinking ability test and data analysis technique included normality test, homogeneity test, and t test. The results showed that there were difference in mathematical creative thinking ability and there were difference in the increase between the classes using Problem Based Learning and the classes using a model of Problem Based Learning with tangram.